2018
DOI: 10.1038/s41598-018-24836-8
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral oxygen saturation and peripheral perfusion in the extremely premature infant with intraventricular and/or pulmonary haemorrhage early in life

Abstract: Extremely preterm infants are at higher risk of pulmonary (PH) and intraventricular (IVH) haemorrhage during the transitioning physiology due to immature cardiovascular system. Monitoring of haemodynamics can detect early abnormal circulation that may lead to these complications. We described time-frequency relationships between near infrared spectroscopy (NIRS) cerebral regional haemoglobin oxygen saturation (CrSO2) and preductal peripheral perfusion index (PI), capillary oxygen saturation (SpO2) and heart ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 90 publications
(124 reference statements)
0
17
0
Order By: Relevance
“…We calculated wavelet and correlation indices in the same piglets during identical physiologic changes from induced hypotension. Clinical neonatal wavelet NIRS methods have also been studied in hypoxic-ischemic encephalopathy 21,22 and prematurity 23 .…”
Section: Discussionmentioning
confidence: 99%
“…We calculated wavelet and correlation indices in the same piglets during identical physiologic changes from induced hypotension. Clinical neonatal wavelet NIRS methods have also been studied in hypoxic-ischemic encephalopathy 21,22 and prematurity 23 .…”
Section: Discussionmentioning
confidence: 99%
“…9 First, extremely premature infants lack adequate cerebral autoregulation compared with more mature preterm infants. Beausoleil et al 10 analyzed cerebral autoregulation, as assessed by near infrared spectroscopy, and demonstrated that cerebral perfusion can fluctuate based on systemic blood pressure greater than 50% of the time in extremely preterm infants compared with 20% of the time in very preterm infants. 11 Changes in systemic blood flow with umbilical cord milking may be transferred to the cerebral blood flow causing rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining optimal perfusion and oxygenation is of prime concern in neonatal intensive care units (NICU). Comprehensive monitoring of various physiological variables is required, as low CO has been associated with increased morbidity, adverse neurodevelopmental outcome, and increased mortality ( 5 ).…”
Section: Introductionmentioning
confidence: 99%